산림작업을 위한 계류식 원형 헬륨기구 기반 Wi-Fi 통신망 시스템의 현장 적용 가능성 평가 - 김균형; Gyun-hyung Kim; 오재헌; Jae-heun Oh; 이현승; Hyeon-seung Lee; 주홍식; Hong-sik Ju; 문호성; Ho-seong Mun; 신범수; Beom-soo Shin (한국산림과학회지, 2025)
목재수확 작업을 수행할 때, 오퍼레이터는 고사목 또는 서로 엉켜있는 나무들로부터 운전석 충돌 가능성과 예측 불가능한 상황이 많아 집중도와 긴장도가 매우 높은 환경에 노출될 수 있으며, 경사지나 불안정한 지형에서 작업 시 기계의 전도·전복으로 인한 인명피해가 발생할 위험도 있다. 이와 같은 문제점은 임업기계에 원격제어 기술을 접목하여 해결할 수 있을 것으로 사료되며, 이를 위해 원격제어를 안정적으로 수행할 수 있는 무선 통신망이 필요할 것으로 판단하였다. 따라서 무선통신망 구축을 위해 계류식 원형 헬륨기구 기반의 Wi-Fi 통신망 시스템을 고려하였으며, 본 연구는 고려된 시스템이 목재수확현장에서 임업기계의 원격제어를 위해 안정적인 Wi-Fi 통신망을 제공할 수 있는지 검증하기 위해 수행되었다. 검증은 GNSS, IMU 그리고 광릉 기상 관측소 데이터를 활용한 풍속별 원형 헬륨기구 자세 및 위치 변화 분석과 임의로 선정한 목재수확 대상지 내에서의 Wi-Fi RSSI(Received Signal Strength Indicator) 분석을 통해 수행되었다. 이 시스템은 1.2 m/s 미만의 풍속에서 약 8.2 ha의 원격제어를 위한 안정적인 Wi-Fi 통신망 구축이 가능할 수 있을 것으로 판단된다. 그러나 1.2 m/s 이상의 풍속에서 원격제어를 위해 시스템을 운용할 시 바람에 저항이 강한 다양한 종류의 헬륨기구를 적용하거나 헬륨기구의 자세를 제어할 수 있는 계류 기술 등 추가적인 연구가 필요할 것으로 판단된다. During timber harvesting, operators face highly demanding and tense working conditions due to risks such as cab collisions with dead trees or entangled stems and frequent unpredictable events. On steep slopes or unstable terrain, there is also a considerable risk of machine overturning and personal injury. These challenges can be mitigated by integrating remote-control technology into forestry machinery; however, reliable wireless communication is essential for stable teleoperation. To address this requirement, a Wi-Fi system supported by a tethered helium balloon was proposed for establishing a communication network. This study assessed whether the system can provide stable Wi-Fi coverage for teleoperation of forestry machinery during timber harvesting. Verification involved analyzing the balloon’s attitude and positional changes under varying wind speeds using global navigation satellite system and inertial measurement unit data, combined with information from the Gwangneung Weather Station, as well as evaluating Wi-Fi received signal strength indicator values at a selected harvesting site. The results indicate that the system can provide stable Wi-Fi coverage of approximately 8.2 ha for teleoperation under wind speeds below 1.2 m/s. At wind speeds above this threshold, further research is required, including testing alternative balloon designs with greater wind resistance or implementing tethering technologies that stabilize balloon orientation.